ANALISIS PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PERILAKU PEGAWAI (Studi Kasus: Badan Kependudukan Keluarga Berencana Nasional Kota Palembang) - Mafra, Nisa` Ulul; Damayanti, Reina (Jurnal Ecoment Global, 2020)
This study is entitled Analysis of the Effects of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on Employee Behavior with a Case Study: National Population Planning Board / BKKBN of Palembang City. Knowing the effect of intellectual, emotional and spiritual intelligence on employee behavior is the aim of this study. The research method used is multiple regression model. Data sources are primary data and secondary data. The research instrument uses a random sampling technique, with a population as well as a sample of 85 BKKBN Palembang City employees. The results showed that employee behavior is influenced by the three intelligences. This is evidenced by the results of the t test of each intelligence (spiritual: 2,465, emotional: 2,155 and spiritual: 8,267) and F test (31,065). While the test of the coefficient of determination (r2) of 0.535 or 53.5% and the remaining 46.5% is influenced by other factors not included in this study, such as rewards, compensation and others. The correlation coefficient is 0.731. This means that these three intelligence variables affect employee behavior and have a strong direct relationship.Keywords: Intellectual Intelligence, Emotional Intelligence Spiritual Inteliigence,Â  Employee Behavior